Prevalence and determinants of unhealthy feeding practices among young children aged 6-23 months in five sub-Saharan African countries. - Berhan Tekeba; Tadesse Tarik Tamir; Belayneh Shetie Workneh; Mulugeta Wassie; Bewuketu Terefe; Mohammed Seid Ali; Enyew Getaneh Mekonen; Alebachew Ferede Zegeye; Gebreeyesus Abera Zeleke; Agazhe Aemro (PLoS ONE)
Introduction Despite the World Health Organization's advice against unhealthy feeding, many low- and middle-income countries, including sub-Saharan Africa (SSA) countries, are experiencing a nutritional transition to high in sugar, unhealthy fats, salts, and processed carbohydrates for younger children. However, there is a scarcity of recently updated multicounty information on unhealthy feeding practices and determinants in SSA countries. Therefore, this study aimed to assess the pooled prevalence of unhealthy feeding practices and determinants among children aged 6-23 months in five SSA countries. Method A cross-sectional study design was employed with the most recent demographic and health survey secondary data (DHS) from five SSA countries. This secondary data was accessed from the DHS portal through an online request. The DHS is the global data collection initiative that provides detailed and high-quality data on population demographics, health, and nutrition in low- and middle-income countries. We used a weighted sample of 14,064 children aged 6-23 months. A multilevel mixed-effect binary logistic regression model was fitted to identify significant factors associated with unhealthy feeding practices. The level of statistical significance was declared with p-value < 0.05. Result This study found that overall, 62.4% (95% CI: 61.62-63.17) of children aged 6-23 months in five SSA countries had unhealthy feeding practices. Rural residents, lower-middle-income SSA countries, and children aged above 12 months had lower odds of unhealthy feeding practices. On the other hand, richer households and women who had not had an optimal antenatal care visit had higher odds of unhealthy feeding practices. Conclusion According to this study, nearly two out of three young children in five SSA countries had unhealthy feeding practices. Both individual and community-level factors are significantly associated with unhealthy feeding practices. As a result, responsible bodies shall make all efforts to reduce unhealthy feeding practices among young children in SSA countries.